Ethnobotanical appraisal of indigenous medicinal plants used in the Taounate region (Northern Morocco): Qualitative and quantitative approaches - Jeddi , Samir; Ferioun, Mohamed; Benkhaira, Nesrine; Jeddi , Mohamed; El Hachlafi, Naoufal; Fikri-Benbrahim, Kawtar (Ethnobotany Research and Applications, 2024)
Background: For centuries, Moroccan population uses medicinal plants as a primary source of medication to treat different human ailments. However, few investigations have been carried out to properly document and preserve this traditional knowledge. Indeed, this ethnobotanical exploration aims to establish an exhaustive inventory of medicinal plants used by the population of Taounate for the treatment of different diseases. Methods: Ethnobotanical surveys were carried out with 500 participants distributed equally between different stations. The study participants were selected randomly and subjected to semi-structured interviews, conducted individually over four months from January to April 2023. The socio-demographic features were evaluated using percentages and frequencies in a simple descriptive statistical analysis. However, the ethnobotanical data involved the use of different methods, such as relative frequency of citation (RFC), family importance value (FIV) and plant part value (PPV). In addition, the data analysis was completed using hierarchical cluster analysis to reveal the similarity between plants and rank these plants based on indexes or frequency in treating diseases. Results: This ethnobotanical survey reported that 112 species of medicinal plants, belonging to 100 genera and 54 botanical families were used for curing a variety of illnesses. Among the 54 families reported, the most predominant are Lamiaceae, with 11 species and a FIV of 22.1%; followed by Apiaceae, with 7 species and a FIV of 1.9% and Asteraceae, with 6 species and a FIV of 8%. Based on hierarchical cluster analysis, Origanum compactum, Rosmarinus officinalis, Salvia officinalis, Pistacia lentiscus and Chenopodium ambrosioides (RFC= 0.366) had the highest values in FC and RFC indexes. Moreover, the heatmap indicates that these plants are primarily used for treating diseases related to the digestive tract (highest ICF values of 0.98). Furthermore, leaves are the most commonly used plant’s part (63%), followed by stem (8%), roots (7%), flowers (5%) and fruit (4%); otherwise, decoction is the most common method (42%), followed by the use of powder (27%) and infusion (13%). The herbal preparation was mainly administered orally (75%). Conclusion: The current study highlights the widespread use of aromatic and medicinal plants in therapy among the Taounate population, forming an integral part of the traditional healing system. This research aims to enhance Moroccan traditional natural heritage while providing researchers with a valuable ethnobotanical database. The latter can serve as an essential resource for more profound research into phytochemistry and pharmacology. Keywords: Ethnobotanical survey; medicinal plants; Taounate; Ethnobotanical indexes; clustering dendrogram analysis.